The Beneficial Angels of Learner-Centered Approach in Prospering Pupils’ Communicative Competence in English Classes at Academic Lyceums - Akhmadalieva Khosiyatposhsho Abdukhayotovna (International Journal on Integrated Education, 2022)
This article deals with the basic role and successful implementation of learner-centered approach in English classes to develop pupils’ communicative competence, as well as, it also focuses the importance of the approach for interactive and effective learning that leads pupils’ more meaningful, interesting and democratic way of acquiring the English language in context of academic lyceum in Jizzakh region, Uzbekistan. Most of the time pupils work individually on tasks and assignments, and group work or collaborative learning is stimulated. Thus, it will improve the ability of pupils to learn the content and they have to prepare variously for the class in order to enhance effective communicative competence.